2009
DOI: 10.1111/j.1525-1470.2009.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Rosai‐Dorfman Disease: Presenting as Massive Bilateral Eyelid Swelling

Abstract: Rosai-Dorfman disease is a rare, benign histiocytic proliferative disorder, which commonly affects the lymph nodes. Cutaneous Rosai-Dorfman disease is a rare form of Rosai-Dorfman disease limited to the skin. We report a case of cutaneous Rosai-Dorfman presenting with bilateral eyelid swelling in a child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
7
1
1
Order By: Relevance
“…[ 4 6 ] Eyelid involvement in Rosai–Dorfman disease is mostly by contiguous spread from adjacent tissues such as orbit or paranasal sinuses. [ 7 8 9 ] A single case with eyelid involvement with isolated cutaneous patches over the chest and legs was reported by Prabhakaran et al ., in their series of five cases presenting in the orbit and adnexal regions. [ 10 ] In a series of seven patients by Vemuganti et al ., two cases presented with eyelid involvement predominantly, although there was involvement of adjacent structures too.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 6 ] Eyelid involvement in Rosai–Dorfman disease is mostly by contiguous spread from adjacent tissues such as orbit or paranasal sinuses. [ 7 8 9 ] A single case with eyelid involvement with isolated cutaneous patches over the chest and legs was reported by Prabhakaran et al ., in their series of five cases presenting in the orbit and adnexal regions. [ 10 ] In a series of seven patients by Vemuganti et al ., two cases presented with eyelid involvement predominantly, although there was involvement of adjacent structures too.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there are a few patients reporting refractory or persistent disease. [ 20 ] There are numerous treatment modalities for cutaneous RDD, including surgical excision, corticosteroids, thalidomide, cryosurgery, radiotherapy, dapsone, isotretinoin, interferon α, acitretin, and pulsed dye laser; all of these agents have shown varying rates of success. [ 21 22 23 24 25 ] In a clinical and histopathologic study of 25 patients with cutaneous RDD, clinical follow-up in 22 patients indicated that surgical excision was the exclusive effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of skin lesions have been described such as infiltrated erythematous/brownish/yellowish papules, nodules, subcutaneous masses, ulcerated nodules, and rosacea‐like lesions affecting most commonly the face but also other parts of the body . Ocular or periorbital lesions including periorbital masses and eyelid lesions have also been reported . Yellowish papules on the eyelids, periorbital area, or rim of the eye concomitant with “xanthelasma‐like” appearance on other parts of the face and extention to the neck, bilateral eyelid swelling, and yellow xanthomatous eyelid masses were some of the reported examples for eyelid lesions.…”
Section: Non‐langerhans Cell Histiocytosesmentioning
confidence: 99%
“…[51][52][53] Ocular or periorbital lesions including periorbital masses and eyelid lesions have also been reported. [53][54][55] Yellowish papules on the eyelids, periorbital area, or rim of the eye concomitant with "xanthelasma-like" appearance on other parts of the face and extention to the neck, 52 bilateral eyelid swelling, 54 and yellow xanthomatous eyelid masses 55 were some of the reported examples for eyelid lesions. Ocular lesions may cause proptosis, blepharoptosis, uveitis, impaired extraocular motility, decreased vision, and diplopia.…”
Section: Reticulohistiocytosismentioning
confidence: 99%